Theissenolactone C Exhibited Ocular Protection of Endotoxin-Induced Uveitis by Attenuating Ocular Inflammatory Responses and Glial Activation - Lin, Fan-Li; Ho, Jau-Der; Cheng, Yu-Wen; Chiou, George C. Y.; Yen, Jing-Lun; Chang, Hung-Ming; Lee, Tzong-Huei; Hsiao, George (Frontiers in Pharmacology, 2018)
The aim of this study was to investigate the effects of a natural component, theissenolactone C (LC53), on the ocular inflammation of experimental endotoxin-induced uveitis (EIU) and its related mechanisms in microglia. Evaluation of the severity of anterior uveitis indicated that LC53 treatment signiﬁcantly decreased iridal hyperemia and restored the clinical scores. Additionally, the deficient retina functions of electroretinography were improved by LC53. LC53 significantly reduced levels of tumor necrosis factor (TNF)-α, monocyte chemoattractant protein-1, protein leakage and activation of matrix metalloproteinases in the anterior section during EIU. Moreover, LC53 treatment decreased the oxidative stress as well as neuroinflammatory reactivities of GFAP and Iba-1 in the posterior section. Furthermore, LC53 decreased the phosphorylation of p65, expression of HSP90, Bax, and cleaved-caspase-3 in EIU. According to the microglia studies, LC53 significantly abrogated the productions of TNF-α, PGE2, NO and ROS, as well as inducible NO synthase and cyclooxygenase-2 expression in LPS-stimulated microglial BV2 cells. The microglial activation of IKKβ, p65 phosphorylation and nuclear phosphorylated p65 translocation were strongly attenuated by LC53. On the other hand, LC53 exhibited the inhibitory effects on JNK and ERK MAPKs activation. Our findings indicated that LC53 exerted the ocular-protective effect through its inhibition on neuroinflammation, glial activation, and apoptosis in EIU, suggesting a therapeutic potential with down-regulation of the NF-κB signaling for uveitis and retinal inflammatory diseases.